CUSTOM MADE INTERNAL AND EXTERNAL NASAL SPLINTS : A COST EFFECTIVE ALTERNATIVE - Waleem, Sheikh Saadat Ullah; Ayub, Muhammad Waqas; Ahmad, Manzoor; Maqbool, Shahzad; Raza, Maqbool; Rahim, Ejaz (Pakistan Armed Forces Medical Journal, 2021)
Objectives: To evaluate the usability and effectiveness of tailor made internal and external nasal splints after nasal surgery. Study Design: An observational study. Place and Duration of Study: Combined Military Hospital Kohat, from Nov 2015 to Aug 2017. Methodology: the study was carried out on 523 patients who underwent nasal surgery by the same team of surgeons. Custom made free of cost internal and external nasal splints were used as required. Complications pertaining to the use of nasal splints were recorded. Results: The custom made splints were found to be an excellent and cost effective alternative of commercially available expensive splints. The benefits and pitfalls were comparable. Conclusion: Where these free of cost splints does the job they as well save a lot of money and can be used as an effective alternative to commercially available splints.